2023
DOI: 10.31275/20232773
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Dying Animals: Parallels With End-Of-Life Experiences in Humans

Abstract: There has recently been an increased interest in end-of-life experiences (ELEs) in humans,but ELEs in non-human animals have not yet been assessed. In this paper, wepresent findings from a study we performed to collect and analyze reports about remarkablebehavioral aspects of animals during their last phase of life. After publicappeals in which we asked for reports about ELEs in animals, we received numerousresponses from pet owners. We were able to group these experiences into specificcategories, which we ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Given the many parallels between human and animal ELEs documented by Sheldrake et al (2023), it is perhaps not surprising to see the parallels extend from peri-mortem to post-mortem phenomena. ADC accounts raise the same questions about the nature and evolutionary development of consciousness as the ELE accounts, elevated to a new level by the suggestion that animal as well as human consciousness survives bodily death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the many parallels between human and animal ELEs documented by Sheldrake et al (2023), it is perhaps not surprising to see the parallels extend from peri-mortem to post-mortem phenomena. ADC accounts raise the same questions about the nature and evolutionary development of consciousness as the ELE accounts, elevated to a new level by the suggestion that animal as well as human consciousness survives bodily death.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up paper, Matlock and Hilton (forthcoming) will delve deeper into our data and consider implications for the understanding of consciousness and the prospect of post-mortem survival of animals as well as humans. Sheldrake et al (2023) showed that the end-of-life experiences of animals are very similar to those of humans. We have taken the next step, demonstrating a close resemblance between after-death communications from animals and from humans.…”
Section: Discussionmentioning
confidence: 99%